1988
DOI: 10.1152/jappl.1988.65.2.662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased pulmonary vascular tone on gas exchange in canine oleic acid pulmonary edema

Abstract: Pulmonary gas exchange was investigated before and after an increase in pulmonary vascular tone induced by administration of acetylsalicylic acid (ASA), indomethacin, or almitrine in 32 pentobarbital-anesthetized and ventilated (fraction of inspired O2 0.4) dogs with oleic acid lung injury. Pulmonary vascular tone was evaluated by five-point pulmonary arterial pressure (PAP)/cardiac index (Q) plots and intrapulmonary shunt was measured using a SF6 infusion. PAP/Q plots were rectilinear in all experimental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 0 publications
3
19
1
Order By: Relevance
“…There were 15 preclinical studies (2640) identified in this systematic review (Table 1). In 10 studies the antiplatelet drug was ASA (2631, 3538) in three studies ASA-triggered lipoxin (32, 33, 38) , and in three studies ASA-triggered resolving D 1 (34, 39, 40) were studied.…”
Section: Resultsmentioning
confidence: 99%
“…There were 15 preclinical studies (2640) identified in this systematic review (Table 1). In 10 studies the antiplatelet drug was ASA (2631, 3538) in three studies ASA-triggered lipoxin (32, 33, 38) , and in three studies ASA-triggered resolving D 1 (34, 39, 40) were studied.…”
Section: Resultsmentioning
confidence: 99%
“…During lung injury, the pulmonary circulation is exposed to the widespread release of these constricting and dilating mediators, the net effect is an increase in the vascular tone. Inhibitors of COX [25,26] and of NO synthesis or their effects, have been shown to further increase Ppa in experimental lung injury [27]. Intravenous infusion of endotoxin in sheep causes Ppa to rise within several minutes, which remains raised for hours [28].…”
Section: Discussionmentioning
confidence: 99%
“…inhibiting HPV) [19]. Blockade of COX and NO have been shown to improve Pa,O 2 by reducing intrapulmonary shunt in animals with oleic acid-induced pulmonary oedema [19,[25][26][27]. In clinical practice, several intravenous vasodilators have been administered in patients with ARDS, with the aim of increasing cardiac output and hence oxygen delivery.…”
Section: Intravenous Vasodilatorsmentioning
confidence: 99%
“…These results are consistent with potentiation of HPV in shunt regions and enhanced diversion of perfusion to ventilated lung. In animal models of ALI/ARDS, these effects of almitrine were shared by antagonists of cyclooxygenase (33, 1058,1060,1738) but not by antagonists of NOS (1058,1415,1555,1668), which increased PVR but did not alter P a O 2 or shunt. These results suggest that endogenous production of vasodilator prostaglandins such as PGI 2 , and thus their inhibition of HPV and other vasoconstrictor mechanisms, may have been greater in more injured nonventilated lung than in less injured ventilated lung, whereas endogenous production of NO and NO-dependent inhibition of vasoconstriction was similar in ventilated and nonventilated lung.…”
Section: Vi) Chronic Obstructive Pulmonary Diseasementioning
confidence: 95%